Treatment outcomes of mucosal melanoma of head and neck: Efficacy of immune checkpoint inhibitors for advanced disease - Ohshima, Shusuke; Ueki, Yushi; Yokoyama, Yusuke; Takahashi, Takeshi; Shodo, Ryusuke; Yamazaki, Keisuke; Okabe, Ryuichi; Matsuyama, Hiroshi; Togashi, Takafumi; Takatsuka, Sumiko; Takenouchi, Tatsuya; Horii, Arata (Frontiers in Surgery, 2022)
Background Head and neck mucosal melanoma (HNMM) is a rare and aggressive subtype of melanoma. HNMM often develops as a recurrent or metastatic disease, and its prognosis is worse than that of cutaneous melanoma. Recent large-scale clinical studies have reported favorable outcomes with immune checkpoint inhibitors (ICIs) for melanoma. However, these clinical trials included only a small number of HNMM cases. This study aimed to estimate treatment outcomes and prognostic predictors of ICIs for advanced HNMM. Methods Cases of advanced HNMM, defined as unresectable or metastatic HNMM at the initial diagnosis (five patients) or development of recurrent/metastatic HNMM after initial treatment (27 patients), were included in this study. Survival analysis and a search for prognostic factors were performed for these 32 patients. Furthermore, the detailed clinical course of patients who received ICI treatment was investigated. Results The median overall survival (OS) of 32 patients with advanced HNMM was 25.3 months. The estimated 1-, 3-, and 5-year OS rates were 68.4%, 42.8%, and 34.3%, respectively. Fourteen patients (43.7%) received ICIs, whereas 18 (56.3%) did not. Univariate analysis showed that ICI treatment was the only factor associated with a better 1-year OS. Patients who received ICI treatment had significantly longer OS (median OS: not reached, 1-year OS: 85.7%) than those who did not (median OS: 11.3 months, 1-year OS: 54.5%). The overall response and disease control rates of patients who received ICI treatment were 50% and 64.3%, respectively. Patients who achieved complete response (CR) or partial response (PR) to ICI treatment survived significantly longer (1-year OS: 100%) than those who did not (1-year OS: 71.4%). Among the five patients who discontinued ICI treatment due to severe immune-related adverse events (irAEs), four did not receive salvage treatments but showed durable treatment effects and survived for 9.8–54.2 months at the end of the follow-up period. Conclusions ICI treatment achieved a favorable OS for advanced HNMM. CR/PR to ICI treatment and discontinuation owing to severe irAEs were favorable predictors of OS.